GC Insights: Nature stripes for raising engagement with biodiversity loss - M. Richardson (Geoscience Communication, 2023)
Globally, there has been a stark decline in biodiversity since 1970, yet climate change receives far greater attention. The “warming stripes” have shown the power of very simple graphical visualisations of data for communicating with broad audiences. The “nature stripes” show how biodiversity data can also be presented in a similar way for a positive effect.